2017
DOI: 10.1016/j.jss.2017.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical progenitor cell therapy in traumatic brain injury: a meta-analysis

Abstract: Background: No treatment is available to reverse injury associated with traumatic brain injury (TBI). Progenitor cell therapies show promise in both pre-clinical and clinical studies. We conducted a meta-analysis of pre-clinical studies using progenitor cells to treat TBI. Methods: EMBASE, MEDLINE, Cochrane Review, Biosis, and Google Scholar were searched for articles using pre-specified search strategies. Studies meeting inclusion criteria underwent data extraction. Analysis was performed using Review Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…MSCs are a similar cell type relative to MAPC, in that they are an adherent, bone-marrow-derived cell, but they differ in terms of ultimate product profile in terms of potency, size, and expansion characteristics. There are numerous publications that report the efficacy of MSCs in animal models of TBI, and this was reviewed in a meta-analysis of preclinical models of TBI using a cellular therapeutic (11). A reported mechanism of action is that cells migrate to the site of injury and exert a paracrine effect by secreting growth factors that preserve at risk neurons.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…MSCs are a similar cell type relative to MAPC, in that they are an adherent, bone-marrow-derived cell, but they differ in terms of ultimate product profile in terms of potency, size, and expansion characteristics. There are numerous publications that report the efficacy of MSCs in animal models of TBI, and this was reviewed in a meta-analysis of preclinical models of TBI using a cellular therapeutic (11). A reported mechanism of action is that cells migrate to the site of injury and exert a paracrine effect by secreting growth factors that preserve at risk neurons.…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…Microglia are the resident myeloid cells within the central nervous system (CNS) parenchyma and are key mediators of the neuroinflammatory response after TBI 3,8,9 . Our lab has investigated the use of cell therapies to attenuate the microglia‐mediated inflammatory response and have found that human mesenchymal stromal cells (MSC) and, recently, human cord blood‐derived regulatory T cell (Treg) therapy both decrease the neuroinflammatory response after TBI 6,10,11 . We believe that a primary mechanism by which cell therapies mitigate the inflammatory response is via interaction with the host immune system, specifically endogenous Treg 10,12 .…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated a strong effect of cell therapy on reducing lesion volume, improving neurosensory (Rota‐Rod) and memory (Morris water maze) outcomes 122 . Preclinical data supports progenitor cell therapy for TBI 123‐125 …”
Section: Introductionmentioning
confidence: 52%